Écriture, histoire et action - Branka Šarančić (Cahiers Balkaniques)
The novel “Death  and the Dervish” is part of those emblematical works which not only escape the traditional codification of the novelistic literary genres but help as well redefine the status itself of literature as an independant means of ideological action. Sometimes read as a historical novel, which plot can be historicaly identified (the Ottoman period), other times read as a political novel, in the tradition of Kafka or Camus, “Death  and the Dervish” is, in the first place, a speech for the defence of artists’ ideological independance. Published in a climate of conflict, where the upholders of the “engaged litterature” (those ones for whom the artistic activities have no sense if they are not subject to some vast social and political project) and supporters of the “pure literature” (those ones who, being concerned about the form, are made heedless of social and political reality) clash, Meša Selimović’s novel aims at redefining the relationship itself between literature and politics by proposing original ideological solutions in both the field of literary creation and of identities representations.